2022
DOI: 10.1002/htj.22784
|View full text |Cite
|
Sign up to set email alerts
|

MHD convective rotating flow of viscoelastic fluid past an infinite vertical oscillating porous plate with Hall effects

Abstract: It is considered the unsteady and incompressible magnetohydrodynamic rotating free convection flow of viscoelastic fluid with simultaneous heat and mass transfer near an infinite vertical oscillating porous plate under the influence of uniform transverse magnetic field and taking Hall current into account. The governing equations of the flow field are then solved by a regular perturbation method for a small elastic parameter. The expressions for the velocity, temperature, and concentration have been derived an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Postelnic 21 determined how radiation, as well as the impacts of Dufour, affect free convective flow in an absorbent material. Raju et al 22 considered the unsteady and incompressible MHD rotating free convection flow of viscoelastic fluid with simultaneous heat and mass transfer near an infinite vertical oscillating porous plate under the influence of uniform transverse magnetic field and taking Hall current into account. Raju and Verma 23 studied the consequences of a chemical reaction in the context of a mass transfer issue based on axial diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Postelnic 21 determined how radiation, as well as the impacts of Dufour, affect free convective flow in an absorbent material. Raju et al 22 considered the unsteady and incompressible MHD rotating free convection flow of viscoelastic fluid with simultaneous heat and mass transfer near an infinite vertical oscillating porous plate under the influence of uniform transverse magnetic field and taking Hall current into account. Raju and Verma 23 studied the consequences of a chemical reaction in the context of a mass transfer issue based on axial diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Raju et al [16] considered the unsteady and incompressible magnetohydrodynamic rotating free convection flow of viscoelastic fluid with simultaneous heat and mass transfer near an infinite vertical oscillating porous plate under the influence of uniform transverse magnetic field and taking Hall current into account. They concluded that the resulting velocity strengthens and encounters deceleration within the flow field as the radiation parameters increase.…”
Section: Introductionmentioning
confidence: 99%